Habituasi Mujahadah Dalam Pembentukan Karakter Santri Di Blok Syauquna Al-Qur’an PPTQ Al-Asy’ariyyah, Kalibeber, Wonosobo - Happy Nurhidayah Putri Pamungkas; Mukromin Mukromin; Faisal Kamal (STIKes Ibnu Sina Ajibarang, 2024)
In language, habituation means habituation, which is what every human being experiences in carrying out the wheel of life. A good habit will certainly produce a good person too. In the teachings of the Islamic religion, we are encouraged to always worship and pray to Allah SWT so that we as His servants will receive blessings in living our lives in this world. One of the many forms of worship and prayer to Allah SWT is Mujahadah. Mujahadah itself comes from the Arabic word